Which "fairness", for whom, and why? An empirical analysis of plural notions of fairness in Fairtrade Carbon Projects, using Q methodology. Issue 56 (February 2016) - Howard, Rebecca J.; Tallontire, Anne M.; Stringer, Lindsay C.; Marchant, Rob A.
Highlights: Uses Q methodology to identify three factors on fairness in carbon projects. Links factors with contested fair trade and carbon processes and practices. Maps key fault lines in fair carbon debates onto theoretical dimensions of fairness. Signals need to make fairness definitions explicit when designing Fairtrade standards. Abstract: Fairness is a relative concept with multiple, subjective and competing notions of what it is, how to achieve it, and for which beneficiaries. Fairtrade International's collaborative efforts to develop a standard to certify Fairtrade Carbon Credits (FCCs) brought together multiple stakeholders in a deliberative context. This paper uses Q methodology to empirically assess the notions of fairness this wider consultation group held. Three distinct 'factors' (or perspectives) are identified, and discussed in relation to a multi-dimensional framework for exploring fairness. The first factor prioritises development delivered through organisations, participation in decision-making and use of minimum prices to adjust trade imbalances. The second factor conceptualises a non-exclusive approach maximising generation and sales of FCCs, involving a commodity chain where everyone performs their optimum function with financial transparency and information-sharing to facilitate negotiations. The third factor involves minimising intervention, allowing carbon commodity chains and project set-ups to function efficiently, and make their own adjustments to enhance benefits access and quality received by beneficiaries. The three factors reflect debates within carbon and fair trade spheres about who should be playing which roles, who should be accessing which benefits, and how people should be supported to interact on an uneven playing field. Communicating findings to standards organisations enables a more open and inclusive policy process. Our research provides a critical reflection on these plural notions of fairness, identifying areas of (dis)agreement within the FCC dialogue, and provides a wider, yet manageable, set of inputs for supporting the FCC process during its inception and subsequent implementation. Clearer definitions of "fairness" are also useful for standards organisations in reviewing ex post whether "fairness" goals have been met.